2021
DOI: 10.1590/1807-1929/agriambi.v25n7p460-465
|View full text |Cite
|
Sign up to set email alerts
|

Improved nutrient uptake in three Crotalaria species inoculated with multifunctional microorganisms

Abstract: HIGHLIGHTS Multifunctional microorganisms promote the nutrient enrichment in Crotalaria plants. Cover crop residues are vital in managing soil fertility. Nutritionally improved cover crops increase soil nutrient levels for the subsequent crop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
(19 reference statements)
0
2
0
2
Order By: Relevance
“…KSM can dissolve K in the soil through the mechanisms of acidolysis, chelation, exchange reactions, and complexation of the organic acids produced [14,61,62]. Likewise, the presence of PSM can make more P available for plant absorption [63]. PSM has been widely accepted as an environmentally friendly and easy-to-obtain P fertilizer for increasing soil orthophosphate concentrations and the geochemical P cycle since the early 20th century [41].…”
Section: The Effect Of Inoculation Soil Microorganisms On Plant Growt...mentioning
confidence: 99%
“…KSM can dissolve K in the soil through the mechanisms of acidolysis, chelation, exchange reactions, and complexation of the organic acids produced [14,61,62]. Likewise, the presence of PSM can make more P available for plant absorption [63]. PSM has been widely accepted as an environmentally friendly and easy-to-obtain P fertilizer for increasing soil orthophosphate concentrations and the geochemical P cycle since the early 20th century [41].…”
Section: The Effect Of Inoculation Soil Microorganisms On Plant Growt...mentioning
confidence: 99%
“…Ello permite mejorar la nutrición vegetal debido principalmente a la solubilización de este nutriente que sintetiza el ácido indol-acético (AIA) (Chagas et al, 2016;Prasad et al, 2020), además de producir diversos metabolitos secundarios entre los que se encuentran otras hormonas de crecimiento como las giberelinas (Argumedo et al, 2009). Estos microorganismos habitan en la rizosfera de las plantas y mejoran la resiliencia de los sistemas de cultivos, ya que, además de promover el crecimiento de las plantas, incrementan su protección contra patógenos e insectos (Lanna et al, 2021).…”
Section: Introductionunclassified
“…Recent studies have shown that the application of bioagents promotes a higher shoot and root biomass production of upland rice (Silva et al 2023); higher grain yield and its components in soybean (Chagas Junior et al 2022); higher leaf contents of N, Fe and Cu in oat plants (Santos et al 2021); and Ca, P, S, Zn and Cu in C. juncea, C. spectabilis and C. ochroleuca (Lanna et al 2021). Therefore, for the diversification of multifunctional microorganisms in a controlled environment, the co-inoculation of Serratia marcencens + Trichoderma koningiopsis provided significant increases in gas rates and yield of common bean (Rezende et al 2021a).…”
Section: Introductionmentioning
confidence: 99%